Rigid and flexible azopolymers modified with donor/acceptor groups. Synthesis and photochromic behavior (eXPRESS Polymer Letters, 2011)
The aim of this work is to investigate the photochromic behavior and nano-structuration capacity of azo-polymers with different architectures and main chain flexibilities, modified with donor/acceptor groups. As a function of the chemical structure and the substitution degree, the azo-polymers can generate physical interactions and lead to different polymer chain conformational re-organization under optical excitation. Nano-structuration experiments were performed on samples with different chemical structures. Surface relief gratings have been realized both in poly(chloromethyl styrene) and polysiloxanes polymers. The complexity of the phenomena that take place under optical excitation of the azo-benzene molecules are reflected by the samples behavior during the nano-structuration process. Preliminary tests to determine the ability of the azo-polysiloxanic films to support cell growth were performed. The films showed remarkable properties to sustain both cell adhesion and proliferation.